Clinical and radiological characteristics of acute pulmonary embolus in relation to 28-day and 6-month mortality. - Lindsey Norton; Gordon Cooper; Owen Sheerins; Killian Mac A' Bháird; Giles Roditi; Michael Adamson; David Young; Ross Dolan; Colin Church; Adrian Brady; Campbell Tait; Graham McKenzie; et al. (PLoS ONE)
Background Patients with acute pulmonary embolism (PE) exhibit a wide spectrum of clinical and laboratory features when presenting to hospital and pathophysiologic mechanisms differentiating low-risk and high-risk PE are poorly understood. Objectives To investigate the prognostic value of clinical, laboratory and radiological information that is available within routine tests undertaken for patients with acute PE. Methods Electronic patient records (EPR) of patients who underwent Computed Tomography Pulmonary Angiogram (CTPA) scan for the investigation of acute PE during 6-month period (01.01.2016-30.06.2016) were examined. Data was gathered from EPR for patients that met inclusion criteria and all CTPA scans were re-evaluated. Biochemical thresholds of low-grade and high-grade inflammation, serum CRP >10mg/L and >150mg/L and serum albumin concentrations <35g/L and <25 g/L, were combined in the Glasgow Prognostic Score (GPS) and peri-operative Glasgow Prognostic Score (poGPS) respectively. Neutrophil Lymphocyte ratio (NLR) was also calculated. Pulmonary Embolus Severity Index score was calculated. Results Of the total CTPA reports (n = 2129) examined, 245 patients were eligible for inclusion. Of these, 20 (8%) patients had died at 28-days and 43 (18%) at 6-months. Of the 197 non-cancer related presentations, 28-day and 6-month mortality were 3% and 8% respectively. Of the 48 cancer related presentations, 28-day and 6-month mortality were 29% and 58% respectively. On univariate analysis, age ≥65 years (p<0.01), PESI score ≥100(p = <0.001), NLR ≥3(p<0.001) and Coronary Artery Calcification (CAC) score ≥ 6 (p<0.001) were associated with higher 28-day and 6-month mortality. PESI score ≥100 (OR 5.2, 95% CI: 1.1, 24.2, P <0.05), poGPS ≥1 (OR 2.5, 95% CI: 1.2-5.0, P = 0.01) and NLR ≥3 (OR 3.7, 95% CI: 1.0-3.4, P <0.05) remained independently associated with 28-day mortality. On multivariate binary logistic regression analysis of factors associated with 6-month mortality, PESI score ≥100 (OR 6.2, 95% CI: 2.3-17.0, p<0.001) and coronary artery calcification score ≥6 (OR 2.3, 95% CI: 1.1-4.8, p = 0.030) remained independently associated with death at 6-months. When patients who had an underlying cancer diagnosis were excluded from the analysis only GPS≥1 remained independently associated with 6-month mortality (OR 5.0, 95% CI 1.2-22.0, p<0.05). Conclusion PESI score >100, poGPS≥1, NLR ≥3 and CAC score ≥6 were associated with 28-day and 6-month mortality. PESI score ≥100, poGPS≥1 and NLR ≥3 remained independently associated with 28-day mortality. PESI score ≥100 and CAC score ≥6 remained independently associated with 6-month mortality. When patients with underlying cancer were excluded from the analysis, GPS≥1 remained independently associated with 6-month mortality. The role of the systemic inflammatory response (SIR) in determining treatment and prognosis requires further study. Routine reporting of CAC scores in CTPA scans for acute PE may have a role in aiding clinical decision-making regarding treatment and prognosis.